Confidence in Teaching Mathematics Among Malaysia Pre-Service Teachers - Md. Yunus, Aida Suraya; Hamzah, Ramlah; Ismail, Habsah; Said Husain, Sharifah Kartini (2006)
This study focuses on the confidence level of mathematics education students in teaching school mathematics. Respondents were 165 final year students from four Malaysian universities. It was found that the respondents showed a strong foundation in mathematics upon entrance to the university. In spite of their strong background in school mathematics, their mean cumulative grade point average (CGPA) during their final year in the university was rather low. The mean confidence level in teaching mathematics was moderate. The respondents showed a relatively high confidence in the pedagogical aspect of teaching. Respondents reported great confidence in teaching Form One to Form Three, however the confidence level declined as the level taught became higher. The confidence level varied with the topics, which was lowest for the topic on probability. Confidence level in solving problems spontaneously during class was low and teaching mathematics in English was the lowest. The results showed that a significant but low positive correlation exists between (i) level of confidence and CGPA and (ii) level of confidence and confidence in implementing specific aspects of teaching. A significant negative correlation was established between (i) level of confidence and CGPA; and (ii) level of confidence and university level mathematics.